Association between COVID-19 morbidity, mortality, and gross domestic product, overweight/ obesity, non-communicable diseases, vaccination rate: A cross-sectional study - Kuat Oshakbayev; Zulfiya Zhankalova; Meruyert Gazaliyeva; Khalit Mustafin; Gulnara Bedelbayeva; Bibazhar Dukenbayeva; Nurzhan Otarbayev; Attila Tordai (Elsevier, 2022)
Background: The spread of COVID-19 depends on a lot of social and economic factors. The aim: to study the influence of country's gross domestic product, population prevalence of overweight/ obesity, NCD mortality, and vaccination on COVID-19 morbidity and mortality rates. Methods: A cross-sectional study with two phases: correlation-regression interrelations in 1) all world countries; 2) all world non-island countries. The study includes the following data from 218 world countries: COVID-19 morbidity/mortality rates, GDP per capita, the prevalence of overweight/ obesity, NCD mortality among adults (both sexes), people fully vaccinated against COVID-19. Results: An average percentage of the prevalence of overweight among adults in world countries by 2019 was 47.31 ± 15.99%, obesity 18.34 ± 9.64%, while the prevalence by 2016 were 39% and 13%, respectively. Overweight and obesity among adults during three years grew by 21.2% and 40.8%, respectively.Data from the world countries provide significant correlations (p < 0.0001) between COVID-19 morbidity, and: GDP (r = 0.517), overweight (r = 0.54), obesity (r = 0.528), NCD mortality (r = 0.537); COVID-19 mortality, and: GDP (r = 0.344), overweight (r = 0.514), obesity (r = 0.489), NCD mortality (r = 0.611); GDP, and: overweight (r = 0.507), obesity (r = 0.523), NCD mortality (r = 0.35), fully vaccinated people (r = 0.754). An increase in fully vaccinated people, from 3% to 30% of world population, decreases new confirmed COVID-19 cases, although the dependence was not significant (p = 0.07).Data from non-island world countries provides more highly significant correlations (p < 0.0001) between COVID-19 morbidity, and: GDP (r = 0.616), overweight (r = 0.581), obesity (r = 0.583); COVID-19 mortality, and: GDP (r = 0.43), overweight (r = 0.556), obesity (r = 0.539); GDP, and: overweight (r = 0.601), obesity (r = 0.633). The differences of correlation coefficients between data of 176 world countries and data of 143 world non-island countries were not significant (Z-scores<1.29; p > 0.05). Conclusion: The study provides evidence of a significant impact of overweight/obesity prevalence on the increase in COVID-19 morbidity/mortality. Countries with higher GDP have a high overweight/obesity prevalence and possibility to get vaccinated.